Membangun Orientasi dalam Bermitra secara Profesional dengan Dasar Etika Bisnis pada PT Banda Arta Jaya Wiguna - Astuti, Vivi Puji; Sunarjo, Wenti Ayu (Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of business ethic and professional competence on partner satisfaction. This research method uses quantitative methods with the sampling technique is purposive sampling and the sample calculation technique is saturated sampling. Where the sample in this study amounted to 91 business partners group 1, form PT Banda Arta Jaya Wiguna. Data were analyzed using multiple linear regression analysis. These results of this study reveal that partially (1) business ethics has a significant positive effect on partner satisfaction, (2) professional competence has a significant positive effect on partner satisfaction, (3) business ethics and professional competence has a significant effect simultaneously on partner satisfaction. The effect of business ethics and professional competence on partner satisfaction is 77,4% while the remaining 22,6% is influenced by other factors not included in this study.